Effects of K+ and Ni2+ substitution on structural,magnetic, electrical transport and electronic properties of charge ordered monovalent-doped pro.75nao.25mn03 manganites / Rozilah Rajmi - Rajmi, Rozilah (2019)
This study involves investigation on physical properties of charge ordered (CO) monovalent-doped orthorhombic Pro.75Nao.25-xKxMn03(x=0-0.20) and Pro.75Nao.25 Mn ixNixO3(x=0-0.10) manganites and density functional theory (DFT) computations of electronic properties of insulating Pro.75Nao.25Mni-;tNix03 (x = 0, 0.25 and 0.50) manganites using LDA+t/method. The CO manganites were substituted with K+ and Ni2+ atNa- and Mn-sites of the Pro.7sNao.25Mn03 respectively, to activate its electronic and magnetic properties. Both substitutions successfully suppressed the CO state and induced ferromagnetic to paramagnetic (FM-PM) transition, accompanied by metal to insulator (M-I) transition. The inducement of FMM-PMI transition for K+-substitution increased Curie temperature (7c) and M-I transition temperature (TMI) which was attributed to the reduction in Mn06 octahedral distortion which leads to the enhancement of double exchange (DE) interaction. Meanwhile, for Ni-substituted samples the induced FMM-PMI transition caused lowering of Tc and TMI which were suggested due to enhanced antiferromagnetic superexchange interactions involving Mn3+-0-Mn3+, Mn4+-0-Mn4+ and Ni2+-0-Ni2+ which decreased the ferromagnetic superexchange interaction between Ni2+-0-Mn4+ leading to reduction of DE interaction. DFT calculation of orthorhombic Pro.75Nao.2sMn03 with FM phase via LDA+C/with UMH =2 eV showed better agreement with the experimental crystal volume and bandgap results. Meanwhile, DFT calculations on orthorhombic Pro.75Nao.25MmxNu03 (x = 0, 0.25 and 0.50) with AFM phase with U value for Mn 3d set at 2 eV (JC = 0) and 6 eV(x = 0.25, 0.50) while for both Pr 4f and Ni 3d the U values were set at 6 eV to compensate for the strong Coulomb repulsion of 3d electrons for Ni. The calculated crystal volume structure and bandgap for Ni free and Ni-substituted (x = 0.25 and 0.50) samples showed better agreement with the experimental data for the selected U values. DOS calculations revealed that all the FM and AFM samples showed half-metallic (HM) character. Partial DOS results showed Mn, Ni and O atoms contributed more significantly to the electronic states at EF for the spin down channel with higher degree of hybridization between the Mn 3d/Ni 3d and O 2p electrons.